SWOT Analysis of Raw Water Source Management at the Regional Drinking Water Company (PDAM) Tirta Hidayah, Bengkulu City - Sahara, Sherly Marta; Saputra, Harius Eko; Rikardo, Yanuar (Social Sciences Journal, 2025)
This study aims to evaluate the strategic management of raw water sources at the Regional Drinking Water Company (PDAM) Tirta Hidayah in Bengkulu City using a SWOT analysis approach. The availability of clean water is a critical component for public health and sustainable development. However, water quality degradation due to pollution and climate change poses significant challenges for public utilities like PDAM. Employing a qualitative descriptive method, the research gathers data through direct observation, in-depth interviews with key stakeholders, and documentation analysis. The findings indicate that PDAM Tirta Hidayah possesses notable strengths, such as the application of modern water treatment technologies, adherence to health regulations including the Ministry of Health Regulation No. 2 of 2023, and a professional operations team. Nevertheless, several weaknesses persist, including limited treatment capacity, inconsistent water quality, high operational costs, and pollution of the Bentiring River, which is the primary water source. Opportunities for improvement lie in adopting advanced water processing technologies, fostering public-private partnerships, and increasing community awareness regarding water conservation. However, external threats such as climate variability and inadequate infrastructure remain pressing issues. Based on the SWOT analysis, a comprehensive strategic plan is recommended to enhance the effectiveness, efficiency, and sustainability of raw water management in Bengkulu. These strategies should address both internal shortcomings and external risks while leveraging existing organizational strengths and market opportunities. This study contributes to the broader discourse on public sector water governance and offers actionable insights for policymakers and utility managers.